2020
DOI: 10.1002/adma.201906614
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reverse Intersystem Crossing Using a TADF‐Type Acceptor Molecule on the Device Stability of Exciplex‐Based Organic Light‐Emitting Diodes

Abstract: Exciplex system exhibiting thermally activated delayed fluorescence (TADF) holds a considerable potential to improve organic light‐emitting diode (OLED) performances. However, the operational lifetime of current exciplex‐based devices, unfortunately, falls far behind the requirement for commercialization. Herein, rationally choosing a TADF‐type electron acceptor molecule is reported as a new strategy to enhance OLEDs' operating lifetime. A comprehensive study of the exciplex system containing 9,9′,9′′‐tripheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 25 publications
1
76
0
2
Order By: Relevance
“…[ 20 ] Works with unimolecular TADF material or bimolecular exciplex‐forming host to sensitizer MR‐TADF emitters have been reported, combining the advantages of both kind materials. [ 16,21 ] Yet, the device performances are still far away from satisfactory. Our work greatly boosts both the device efficiency and stability, testifying the crucial importance of proper TADF sensitizer and the effectiveness of the molecule design strategy here.…”
Section: Figurementioning
confidence: 99%
“…[ 20 ] Works with unimolecular TADF material or bimolecular exciplex‐forming host to sensitizer MR‐TADF emitters have been reported, combining the advantages of both kind materials. [ 16,21 ] Yet, the device performances are still far away from satisfactory. Our work greatly boosts both the device efficiency and stability, testifying the crucial importance of proper TADF sensitizer and the effectiveness of the molecule design strategy here.…”
Section: Figurementioning
confidence: 99%
“…To overcome these limitations, fewer studies have been reported on the long operational lifetime of blue TADF‐OLEDs. [ 18–22 ] S. G. Ihn et al reported indolocarbazole and pyrimidine‐based TADF emitter, 5,8‐bis(4‐(2,6‐diphenylpyrimidin‐4‐yl)phenyl)‐5,8‐dihydroindolo[2,3‐c]carbazole (BDpyInCz) with a long‐delayed exciton lifetime of 32 µs. [ 18 ] However, their device exhibited a low external quantum efficiency (EQE) (12%) and device lifetime (LT 80 ) of only 8 h at the initial luminance of 500 cd m −2 with deep‐blue color coordinates of (0.16, 0.20).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum EQE and brightness of 8.9% and 830 cd/m 2 and 19% and 1,260 cd/m 2 for the devices with and without ν-DABNA were observed. Further, the LT 50 lifetime of both devices showed almost similar values (∼350 h) and indicates the promising way of making stable devices (Nguyen et al, 2020). Recently, Oda et al (2019) reported two multiple resonance-based TADF materials, ADBNA-Me-Mes and ADBNA-Me-Tip; these materials possess one nitrogen atom in the center of the core and two boron atoms in the outer of the core unit.…”
Section: Multiple Resonance-based Structure For Blue Thermally Activamentioning
confidence: 71%
“…This is the highest efficiency of multiple resonancebased TADF materials reported so far. Recently, Nguyen et al (2020) evaluated the performances of exciplex host-based TADF devices, and they compared the device performances with and without ν-DABNA as 1 wt% emitting dopant. The maximum EQE and brightness of 8.9% and 830 cd/m 2 and 19% and 1,260 cd/m 2 for the devices with and without ν-DABNA were observed.…”
Section: Multiple Resonance-based Structure For Blue Thermally Activamentioning
confidence: 99%